Analisis Atas Pengenaan, Penyetoran dan Pelaporan Pajak Pertambahan Nilai Yang Dilaksanakan Oleh PT. XYZ - Eliza, Eliza,; Retno Wulandari; Taufik Hidayat (LPPM-STPI, 2020)
Ease is a demand of the people in this modern era, the self-assessment system adopted by Indonesia in terms of taxation, which gives responsibilities to taxpayers to reportthe tax payable. Ease of calculation, calculating and reporting tax payable.This research outline aims to find out whether the calculation of deposit and reportingof PT XYZ value added tax is in accordance with the provisions of the tax laws. Are there anyobstacles in the implementation of value added tax collection. How are the efforts made bythe company to overcome these obstacles.The study was conducted with a descriptive analysis method which is an observation ofthe object of the interview with informants relating to research problems and literaturestudies.